2014
DOI: 10.1542/peds.2013-3334
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unplanned Extubations in the NICU

Abstract: BACKGROUND AND OBJECTIVES: Unplanned extubation can be a significant event that places the patient at risk for adverse events. Our goal was to reduce unplanned extubations to <1 unplanned extubation per 100 patient-intubated days. METHODS: All unplanned extubations in the NICU beginning in October 2009 were audited. Data collected included time of day, patient weight, and patient care activity at the time of the event.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 15 publications
1
63
0
14
Order By: Relevance
“…Mbi Ndakor et al . report that a rate of <2 per 100 days was adopted by an American network following the Vermont Oxford Network's iNICQ Collaborative on Controversies in Respiratory Care (2012); however, Merkel et al . suggest that the rate should be <1 per 100 patient intubated days.…”
mentioning
confidence: 99%
“…Mbi Ndakor et al . report that a rate of <2 per 100 days was adopted by an American network following the Vermont Oxford Network's iNICQ Collaborative on Controversies in Respiratory Care (2012); however, Merkel et al . suggest that the rate should be <1 per 100 patient intubated days.…”
mentioning
confidence: 99%
“…Other studies [5,1618] report similar findings in different populations. Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU. In summary, our findings and those of other studies [5,1618] indicate that a multidisciplinary quality improvement program can effectively reduce UE in the ICU, and the effect can be maintained and even improved 15 years after the sequential introduction of different interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta mesma perspectiva, o artigo 02 apresenta um pacote de práticas que podem ser implementadas para reduzir as ENP, como a educação do pessoal, a frequência e importância de ENP, priorizando a segurança do TET, colocação de cartões coloridos para alertas de vias aéreas na cabeceira de cada paciente entubado e/ou ventilado mecanicamente, uso de um dispositivo comercial para proteger o tubo e a análise de qualquer ENP por uma equipe multidisciplinar. Essas medidas são de total importância para a diminuição significativa da taxa de ENP como descrito no estudo mencionado (12) .…”
Section: Discussionunclassified